Evaluation of the Viscosity of Terrafloc Polymer and Xanthan Gum Polymer - Amri, Sulthoni; Setiati, Rini; Fathaddin, Muhammad Taufiq; Rakhmanto, Priagung; Swadesi, Boni; Ratnaningsih, Dyah Rini (Penerbitan Universitas Trisakti, 2024)
Polymer injection is one of the EOR methods using chemical which is injected into the reservoir to increase oil recovery. The polymer functions to maintain the flow of fluids, especially water, so that it does not boil ahead of oil towards production wells. This is due to the ability of the polymer to increase the viscosity of the fluid in the reservoir. The polymers commonly used in the petroleum world are synthetic polymers and natural polymers which are often referred to as biopolymers. The type of biopolymer in this article is Xanthan Gum while the synthetic polymer used is Terrafloc. The characteristics of these two polymers are compared so that the performance that will be obtained in an effort to increase the recovery of petroleum can be estimated. From the results of the viscosity measurement, it turned out that the Xanthan Gum polymer had a much greater viscosity value than the Terrafloc polymer. Thus, the use of Xanthan Gum and Terrafloc polymers can be adjusted to the needs related to the type of crude oil in the reservoir to be injected so that the results of obtaining petroleum can be optimal.